Ocorrência de ondas de calor no triângulo mineiro e alto paranaíba e seu efeito na produção leiteira e consumo alimentar em bovinos - Nascimento, Carolina Cardoso Nagib [UNESP]; Nascimento, Mara Regina Bueno de Mattos; da Silva, Natascha Almeida Marques (My University, 2014)
The aim of this study was to estimate milk production and food consumption during the occurrence of heat waves in the Triângulo Mineiro and Alto Paranaíba, MG by means of bioclimatic zoning based on the Temperature and Humidity Index (THI). Therefore a history of heat wave occurrence between the years 2000-2010 was compiled. The decline in milk production (DMP) and reduced food consumption (RFC) were simulated in cities where periods of heat waves were identified. Frutal and Ituiutaba had the highest rate of heat wave occurrence per year. The DMP and RFC showed bioclimatic differences between the cities of Uberaba, Ituiutaba and Frutal. The cities with the best bioclimatic conditions were Sacramento and Patrocinio, as they presented a THI classified outside of the emergency range, with a night THI of below 76 and without heat waves. Therefore, the occurrence of heat waves can impair food intake and decrease milk production, thereby most effectively demonstrating the effects of thermal stress on dairy cows in the Triângulo Mineiro and Alto Paranaíba, MG region.
Occurrence of heat waves in triangulo mineiro and alto paranaíba and their effect on milk yield and feed intake in cattle
Keywords: Bioclimatic zoning; Climate change; Dairy cattle; Thermal stress